134k views
4 votes
What is the 7th term in the geometric sequence described by this explicit formula?an = –3 • (3)(n – 1)

2 Answers

3 votes

Answer:

7th term is -2187

Explanation:

Nth term of the geometric sequence is given by


a_n = a_1(r)^(n-1)

where a1 is the first term and 'r' is the common ratio


a_n = -3(3)^(n-1)

a1=-3 and r=3

7 th term of the geometric sequence is


a_7 = a_1(r)^(6)

replace the values of a1 and 'r'


a_7 = -3(3)^(6)

a_7=-2187

User Max Yao
by
6.9k points
5 votes

Answer:

7th term = -2187


Explanation:

The formula for nth term of a geometric sequence is given by:


a_n=a*r^(n-1)

Where

  • a is the first term,
  • r is the common ratio,
  • n is the nth term (term number)

Since the question gives us the formula and wants to know 7th term, we just plug in 7 into n:


a_n=(-3)*(3)^(n-1)\\a_n=(-3)*(3)^(7-1)\\a_n=(-3)*(3)^6\\a_n=-2187


User DerVO
by
6.8k points